Gestational trophoblastic neoplasia with cardiac metastasis and multiple embolic manifestations: A rare case report (Asian Journal of Medical Sciences, 2025)
Gestational trophoblastic neoplasia (GTN) is a highly treatable malignancy with cure rates of approximately 100% in low-risk and 90% in high-risk cases. This report details an 18-year-old primigravida diagnosed with high-risk GTN after preterm intrauterine death, presenting with significant vaginal bleeding and an elevated beta-human chorionic gonadotropin level exceeding 300,000 mIU/mL. Imaging revealed a large uterine mass with myometrial invasion and pulmonary metastasis. With a World Health Organization risk score of 8, the patient experienced severe embolic complications, including transient ischemic attacks and infarcts. Treatment involved multi-agent chemotherapy, anticoagulants, and antibiotics, which led to complete regression of the cardiac mass and remission after four cycles. This case highlights the challenges in the risk stratification and management of GTN with unusual metastatic sites, such as the heart. The independent high-risk factor of tumor age, highest in GTN following term pregnancy, may explain the propensity for unusual metastatic sites and poorer prognostic importance of timely diagnosis and treatment for optimal outcomes.